Effects of different mulches and net house on crucifer aphid (Brevicoryne brassicae L.) population, growth and yield of broadleaf mustard (Brassica juncea) - Regmi, Rajendra; Poudel, Sanjay; Shrestha, Arjun Kumar; Thapa, Resham Bahadur; Tiwari, Sundar (Journal of Agriculture and Natural Resources, 2021)
Crucifer aphid, Brevicoryne brassicae, is a key pest of broadleaf mustard and other crucifers. An alternative integrated management approaches are recommended to keep the pest below economic threshold level. A field experiment was carried out to evaluate the effect of mulching and net house on aphid population, growth and yield of broadleaf mustard. Experiment was carried out in randomized complete block design with four replications from September to December 2016 at Rampur, Chitwan, Nepal. Five treatments used in experiment was untreated control, black plastic mulch only, reflective plastic mulch only, black plastic mulch plus imidacloprid 70 WSG @ 0.13gm/liter, and net house plus black plastic mulch. The results showed that the lowest population of crucifer aphid was recorded inside the net house with black plastic mulch and black plastic mulch with imidaclorpid 70 WSG @ 0.13g/L spray. Reflective plastic mulch was superior as compared to black plastic mulch and control to reduce the aphid population. Similarly, the highest yield (26.86t/ha) was obtained inside the net house with black plastic mulch followed by black plastic mulch with imidacloprid spray (25.99 t/ha). But the benefit-cost ratio was the highest (4.09) in black plastic mulch with imidacloprid spray followed by reflective plastic mulch (3.42), black plastic mulch (3.32), and net house with black plastic mulch (3.10). Benefit-cost ratio was lower in net house with black plastic mulch but products are safe from toxins and potentially profitable in long run. Considering its ecological cost, the use of pest exclusion net is recommended as a viable option for controlling insect pests of broadleaf mustard.